Exploring Obstacles Experienced by Learners with High-Functioning Autism in Pursuing Careers in Sports - Mushambi, Charles; Diale, Boitumelo; Sefotho, Maximus Monaheng; Eseadi, Chiedu (Bulletin of Counseling and Psychotherapy, 2024)
This study investigated the obstacles faced by learners with high-functioning autism in pursuing careers in sports, at a special school in Johannesburg, South Africa. It explored strategies that these learners can use to overcome obstacles they may experience in pursuing careers in sports. The study used a qualitative methodology informed by an interpretive paradigm and intrinsic case study design. The study involved eighteen participants, namely six teachers, six parents and six learners. Data were collected through focus group interviews, semi-structured interviews, art-based career collages and document analysis. The data were analyzed through thematic analysis. The findings show that these learners face numerous obstacles in pursuing sports careers due to a lack of resources, inadequate facilities, lack of parental involvement, discrimination, inadequate training of teachers, lack of sporting activities, and lack of appropriate school structures. The learners face personal obstacles, including verbal, writing, social, interactional, and behavioral deficiencies. The findings indicate a need to provide these learners with adequate and relevant resources and facilities at home, school, and elsewhere to tackle these obstacles.